Pengaruh Youtube Sebagai Media Pembelajaran Terhadap Motivasi Belajar Matematika Siswa Kelas V Gugus 8 Kabupaten Lebong - Putra, Rinaldi Jaya; Agusdianita, Neza; Juarsa, Osa (JURIDIKDAS, 2025)
This study aims to analyze the effect of using YouTube as a learning medium on the motivation to learn mathematics in class V cluster 8 Lebong Regency. This type of research is a quantitative research using quasi-experimental/quasi-experimental methods, and the research design used is the matching only pretest posttest control group design. The population in this study were all SDN cluster 8 Lebong Regency, and the sample selection used cluster random sampling, with the sample being at SDN 18 Lebong for the control class, and SDN 75 Lebong for the experimental class. Data collection used a closed questionnaire with a Likert scale measurement. The results of the research show that tcount is 18.304 and ttable with a significance level of 2.145, so with tcount 18.304 > ttable 2.145 it can be concluded that there is an effect of using YouTube as a learning medium on the motivation to learn mathematics in class V class 8 Lebong district.